Transcriptome Analysis Between Parents and Offspring Revealed the Early Salt Tolerance Mechanism of Rice NGY1 - Cheng Li; Kai Lu; Wen-Hua Liang; Tao Chen; Shu Yao; Lei He; Xiao-Dong Wei; Ling Zhao; Li-Hui Zhou; Chun-Fang Zhao; Qing-Yong Zhao; Zhen Zhu; et al. (Rice)
Abstract Salt stress poses a severe threat to global rice productivity, and developing salt-tolerant cultivars represents a critical strategy to address this challenge. However, the molecular mechanisms underlying salt tolerance in rice remain elusive. This study focuses on NGY1, a crossbred offspring between YF47 and SN9903, which showed superior salt tolerance compared to its parent lines during the seedling stage. RNA sequencing (RNA-seq) of seedlings harvested at distinct temporal stages of salt stress identified over 10,000 differentially expressed genes (DEGs). Functional enrichment analyses (GO and KEGG) revealed that NGY1 uniquely mobilized a broader repertoire of stress-responsive genes within shorter timeframes than its parents lines, particularly those associated with redox homeostasis, phytohormone signaling, and MAPK cascades. Meanwhile, NGY1 can rapidly upregulate genes related to salt tolerance compared to its parent during the initial stress phase. Additionally, differences in salt tolerance between NGY1 and its parents were linked to variations in alternative splicing and the high expression of certain NBS-LRR protein genes early in salt stress exposure. These findings not only provide new insights into the molecular mechanisms of salt tolerance, but also provide a theoretical basis for genetic improvement of salt tolerance in rice.